An Econometric Analysis of Tax Evasion and Its Consequences on Economic Performance - Abdullah M. Ghazo; Qusay M. Qasrawi; Ziad M. Abu-Lila (Ital Publication, 2021)
This study aimed to estimate the extent of tax evasion in Jordan based on a currency demand methodology, the results of the time series stationarity test showed that there was a time series to be non-stationary at the same degree, and the results of the co-integration test showed the existence of co-integration between the model variables, the size of tax evasion during the period 1980–2019 was estimated using the fully modified ordinary least squares method (FM-OLS).The results showed that the average rate of tax evasion as a percentage of (GDP) amounted to 2.7%, whereas it reached 16.7% of tax revenues, After the extent of tax evasion had been estimated, its impact on some macroeconomic variables was identified through the Toda and Yamamoto causality test, This test showed that tax evasion had an impact on the general consumer price index, GDP, tax revenues, public debt, both public and private investment, and both public and private consumption, Finally the study recommends that more attention should be paid to the tax evasion phenomenon by officials in charge of economic policies and tax administration in order to reduce tax evasion and its impact on the economic variables and, thus, achieve greater economic stability. Doi: 10.28991/esj-2021-01271 Full Text: PDF